IN-HOSPITAL OUTCOMES AMONG PATIENTS PRESENTED WITH ST-ELEVATION MYOCARDIAL INFARCTION TREATED WITH PRIMARY PERCUTANEOUS CORONARY INTERVENTION - JAN , MT; KHAN , MA; NOMAN , M; ULLAH , H; ALAM , K; RIAZ, M (Biological and Clinical Sciences Research Journal, 2024)
Primary Percutaneous Coronary Intervention (PCI) is considered the gold standard treatment for patients with ST-elevation myocardial Infarction (STEMI). Prompt intervention, aimed at restoring blood flow, plays a critical role in improving survival and minimizing complications in these patients. Objective: The objective of this study was to evaluate in-hospital outcomes among patients diagnosed with STEMI and treated with Primary PCI. Methods: This cross-sectional study was conducted in the Cardiology Department over one year. The study included patients aged 50 years and older who were diagnosed with STEMI based on electrocardiographic criteria and presented within 12 hours of symptom onset. Demographic information, clinical characteristics, comorbidities, and in-hospital outcomes were recorded. Statistical analyses were performed using relevant descriptive measures. Results: A total of 150 patients were included in the study. The mean age of patients was 60.89 ± 5.65 years, with 64.4% being male. The average door-to-balloon time was 89.93 ± 18.12 minutes. Successful reperfusion, defined as achieving a TIMI grade 3 flow, was observed in 87.8% of the patients. In-hospital mortality was recorded at 4.4%, while 3.3% of patients developed infections during their hospital stay. Conclusion: The study demonstrated favourable in-hospital outcomes for STEMI patients treated with Primary PCI, with a high success rate in achieving TIMI grade 3 flow and a relatively low in-hospital mortality rate. These findings underscore the efficacy of timely PCI in improving survival and procedural outcomes in STEMI patients, particularly when door-to-balloon time is minimized.